TI in the Institutional Scientific Productivity of Ecuador, Cuba and Colombia - Lisbet Eunice Pérez Anzardo; Rodolfo González Ortega; Pedro Bruzón Sosa; Catia Ruiz Bosch (Budapest International Research and Critics University, 2022)
Scientific production is one of the indicators of relevance to measure the efficiency in the institutional environment, which implies a development conditioned in all the sectors from the society to world level. In the same way, the technologies of the information (TI) represent a decisive element for their administration which has experienced a constant growth during the last decades similar to the consolidation of the university studies in the different areas of the knowledge and study modalities. The following article makes a reflection on the base of the concepts and tendencies of the scientific investigation and its linking with the technologies of the information. The production of the investigation was characterized in the countries of Ecuador, Cuba and Colombia, as well as the existent relationship among the investment in technologies of the information and the institutional productivity, which was performed with the analysis of bibliometric indicatives. As a result, it was set down the bases for the theoretical-practical deeping of the investigation. Also, it was verified that the investment in IT focused in articles and scientific magazines, contribute to a better knowledge in academic institutions and that the three countries develop policies to motivate this activity, being Colombia the one with more production in the last ten years, as well as the one that has had bigger expense in IT as percentage of the GDP, which is carried out mainly by the government; although the administration of the knowledge has a transcendental impact for the economic and social development of any country.